Effect of Temperature on Photonic Band Gaps in Semiconductor-Based One-Dimensional Photonic Crystal. (29th August 2013) - Malik, J. V.; Jindal, K. D.; Kumar, Vinay; Kumar, Vipin; Kumar, Arun; Singh, Kh. S.; Singh, T. P.
Abstract : The effect of the temperature and angle of incidence on the photonic band gap (PBG) for semiconductor-based photonic crystals has been investigated. The refractive index of semiconductor layers is taken as a function of temperature and wavelength. Three structures have been analyzed by choosing a semiconductor material for one of the two materials in a bilayer structure. The semiconductor material is taken to be ZnS, Si, and Ge with air in first, second, and third structures respectively. The shifting of band gaps with temperature is more pronounced in the third structure than in the first two structures because the change in the refractive index of Ge layers with temperature is more than the change of refractive index of both ZnS and Si layers with temperature. The propagation characteristics of the proposed structures are analyzed by transfer matrix method.